Expression and prognostic significance of NKD2 in ovarian cancer. (15th December 2020) - Wei, Wei; Zheng, Lisi; Gao, Ying; He, Minjun; Yang, Fan
Abstract: Purpose: Naked2 (NKD2) is a negative regulator of Wnt signaling pathway and associates with transforming growth factor secretion. The role of NKD2 in ovarian cancer is unknown. Patients and methods: Gene expression profiles were measured and compared in nine patients by RNA sequencing. NKD2 expressions in ovarian cancer were measured by reverse transcription polymerase chain reaction and western blot. Tissue slides of 79 patients were stained and scored for NKD2 expression. In vitro experiments were conducted to explore the role of NKD2 in ovarian cancer. The prognostic role of NKD2 was evaluated by survival analysis. Results: NKD2 was upregulated in patients with better survival by mRNA and protein expression. Patients were classified as NKD2-high group ( n = 30) and NKD2-low group ( n = 49) according to immunohistochemical score. High NKD2 was correlated with lower recurrence rate ( P = 0.002) and higher percentage of platinum-sensitive recurrence ( P = 0.006). Median progression-free survival was significantly longer for NKD2-high patients than NKD2-low patients (49.1 vs.14.1 months, P < 0.001). Accordingly, there was a significantly difference in terms of overall survival time between two groups (hazard ratio: 3.04; 95% confidence interval: 1.58–5.85, P < 0.001). Multivariate regression suggested that NKD2 was independently prognostic factors in terms of progression-free survival (hazard ratio: 2.91; 95% confidence interval: 1.61–5.27, P < 0.001) and overall survival (hazard ratio: 3.6; 95% confidence interval: 1.80–7.21, P < 0.001). In vitro studies further demonstrated that NKD2 suppressed ovarian cancer cell proliferation, colony formation and cell migration. Conclusion: NKD2 is a novel prognostic marker and could suppress tumor progression in ovarian cancer. Abstract : Ovarian cancer patients with high immunohistochemical score of NKD2 had significantly longer progression-free survival and overall survival than their counterparts. NKD2 impaired ovarian cancer proliferation and migration in vitro .